Mesoamerican religions and archaeology : essays in pre-Columbian civilizations - Bošković, Aleksandar (Archaeopress pre-Columbian archaeology, 2017)
The main goal of this work is to produce a methodologically sound and ethically valid interdisciplinary introduction into the exciting world of ancient Mesoamerica.